Returns to Islamic Microfinance: Evidence from a Randomized Experiment in Pakistan - Maazullah,; Arjun S. Bedi (Institute of Labor Economics (IZA), 2017)
The global microfinance movement is driven by the claim that once poor micro-entrepreneurs are provided access to capital, they will be able to generate high returns. The existing evidence on returns to capital is mixed and too limited to substantiate this claim. This paper reports on a field experiment conducted in Pakistan, in co-operation with Akhuwat microfinance, in which interest free loans were randomly provided to microenterprises. We find that treatment leads to a significant increase in working capital and in business profits. Using randomized treatment as an instrument for capital, we find average monthly returns to capital of 8.6 to 11.9 a month. These returns are substantially higher than the interest rates charged by microfinance institutions in Pakistan.
Keywords: O17; O16; C93; 330; returns to capital; microfinance; microenterprises; randomized experiment; Akhuwat microfinance